2009
DOI: 10.1080/17482960902803440
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with lithium carbonate does not improve disease progression in two different strains of SOD1 mutant mice

Abstract: It has been shown that chronic treatment with lithium carbonate (Li(2)CO(3)) in presymptomatic SOD1G93A transgenic male mice, a model of ALS, was able to remarkably increase their lifespan through the activation of autophagy and the promotion of mitochondriogenesis and neurogenesis. This prompted us to test the lithium effect also in female SOD1G93A mice with two phenotypes of different disease severity. Female SOD1G93A mice of C57BL/6J or 129S2/Sv genetic background were treated daily with Li(2)CO(3) 37 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 16 publications
4
85
0
Order By: Relevance
“…Concurrently, other groups attempted to reproduce the preclinical data and could not 12,13 . Although it is difficult to determine why the first study showed such a dramatic effect, its initial results are curious.…”
Section: Four Ways To Fight Noisementioning
confidence: 99%
“…Concurrently, other groups attempted to reproduce the preclinical data and could not 12,13 . Although it is difficult to determine why the first study showed such a dramatic effect, its initial results are curious.…”
Section: Four Ways To Fight Noisementioning
confidence: 99%
“…Most researchers strongly suspect that the lack of success, including translational efficacy, of preclinical studies in ALS/MND is due to the use of one single rodent model, the transgenic SOD model carrying a high number of G93A mutations (16). Although its use remains justified as results are rapidly achieved, there are some major concerns:…”
Section: Sod1 Rodent Modelsmentioning
confidence: 99%
“…Because defective autophagy has been found in diseased motor neurons (Venkatachalam et al, 2008), the autophagy-inducing properties of lithium are also believed to contribute to its protective effects in ALS (Fornai et al, 2008;Fulceri et al, 2011). However, one recent study in a female mouse ALS model found that lithium had no beneficial or neuroprotective effects (Pizzasegola et al, 2009). Although differences in sex and the genetic background of the mice cannot be excluded, the remarkably low serum steady-state lithium level (0.05-0.07 mM) found in these female mice from the latter study may account for this discrepancy.…”
Section: E Alsmentioning
confidence: 99%